Productos mediáticos: El affairBelsunce y el suspenso permanente de la realidad - Hortiguera, HUGO (Estudios sobre el Mensaje Periodístico, 2005)
The idea of “permanent suspense of the political and social reality” is not new in Argentine culture. However, what is particularly unusual is the exaggerated way this notion develops in the last decade - how it comes to circulate socially, how it is used by the Argentine media, and how it becomes articulated with a range of (para)literary genres to explain a variety of issues of national concern. This paper argues that the Argentine media develop a particular discourse concerned with demonstrating both the disappearance of certain ethical values and the danger of social dissolution and disintegration entailed therein. A space of tension is created by and in the media in which elements of the feuilleton and the thriller are merged (see Martín-Barbero and Rey 1999, Cantón 2002 and Link 2003b). Exemplifying with articles from Clarín, La Nación and Página 12 concerning a famous criminal case (the murder of María Marta García Belsunce), this paper describes how this space is constructed, its characteristics and the discussions which these articles give rise to concerning rules of representation in the press.
Keywords: crime stories; paraliterature; construction of meaning; irresolution